2021
DOI: 10.1038/s41586-021-04195-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic evolution of phytoplankton forced by changes in tropical seasonality

Abstract: The effect of global climate cycles driven by Earth's orbital variations on evolution is poorly understood because of difficulties achieving sufficiently-resolved records of past evolution. The fossil remains of coccolithophores, a key calcifying phytoplankton group, enable an exceptional assessment of the impact of cyclic orbital-scale climate change on evolution because of their abundance in marine sediments, and because coccolithophores demonstrate extreme morphological plasticity in response to the changin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 75 publications
2
30
0
Order By: Relevance
“…Within A1, intra-specific divergences then occurred through different events of vicariance during the MIS4-2 glacial period, establishing genetically distinct populations along a latitudinal gradient. A significant eccentricity minimum associated with these events could account for interactions between newly diversified populations within A1 due to stronger compression of ecological niches [ 69 ]. In this scheme, gene-flow between emerging populations could have played a role in the adaptive process associated with expanded habitat to higher latitudes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within A1, intra-specific divergences then occurred through different events of vicariance during the MIS4-2 glacial period, establishing genetically distinct populations along a latitudinal gradient. A significant eccentricity minimum associated with these events could account for interactions between newly diversified populations within A1 due to stronger compression of ecological niches [ 69 ]. In this scheme, gene-flow between emerging populations could have played a role in the adaptive process associated with expanded habitat to higher latitudes.…”
Section: Resultsmentioning
confidence: 99%
“…Gene flow events within A1 redistributed allelic composition associated with common ancestors of the three lineages into newly formed populations, contributing to potential adaptation to environmental variability along latitudinal gradients. The 400 ky cycle of the absolute eccentricity minimum, which had not occurred since the origin of the G. huxleyi lineage, may be related to major events of diversification within Gephyrocapsa [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it has long been recognized that key questions involving the molecular, morphological and physiological diversity of the group are best explored with combinations of expertise found within the fields of biology and earth sciences [171,172]. The promise of combining molecular techniques with detailed fossil time series data is exemplified in recent studies of E. huxleyi and its closest relatives [57,58,103]. Expanding this approach to include other key coccolithophore clades will be crucial in exploring the hypothesized differences in evolutionary rates or adaptive strategies between clades [83,173].…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that interspecific hybridization and gene exchange is a very recent phenomenon in these blooming coccolithophores [58], confirming that the group continues to diversify today, on the adaptive radiation trajectory that started in the latest Miocene-Pliocene [102] (see also Figure 6b). A second, alternative hypothesis involves a role of long (405,000 year) orbital cycles forcing the repeated pattern of size expansions and contractions within the Noelaerhabdaceae over the past 2.8 Myr [103]. The eccentricity of Earth's orbit around the sun influences seasonal contrasts, which in turn determine the phytoplankton seasonal succession and the number of available niches in the photic zone.…”
Section: Modes Of Speciation In Coccolithophoresmentioning
confidence: 99%
“…However, some analogy might be drawn in our understanding of how climate change affects biodiversity because, as recently demonstrated in the Quaternary, rapid phenotypic size changes in calcareous nannoplankton almost always imply speciation events, which appear to be related to significant climate changes (Bendif et al, 2019;Beaufort et al, 2022). Moreover, direct causal factors that can be invoked for size variation in plankton may be indirectly related to temperature and, in fact, driven by other factors, like fertility and light availability.…”
Section: Arementioning
confidence: 99%